Zamieranie jesionu wyniosłego (Fraxinus excelsior L.) w rezerwacie Jesionowe Góry - Orzechowski, Michał; Kacprzak, Jakub; Kędziora, Wojciech (Leśne Prace Badawcze, 2016)
The aim of this study was to analyse changes in the health status of ash stands belonging to the age classes VI and VIII growing in optimal site conditions and to compare the ash dieback with other age classes in the Jesionowe Góry Nature Reserve. Our research was conducted during the growing season in 2006 and 2007 on 22 permanent and 54 temporary sample plots. The health condition of the stands and the structure of natural regeneration were determined with a one-year interval. The amount of damage was defined using leaf loss, pest infestation and shoot dieback. Based on our estimation of natural regeneration, the capability for stand evolution in the future was determined.